GAMBARAN KARAKTERISTIK IBU HAMIL DENGAN PRE EKLAMPSI BERAT - Sibuea, Elizabeth Agustina (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Severe pre eclampsia (PEB) is a complication that is characterized by the onset ofhypertension 160/110 mm Hg or more with proteinuria and or / edema at 20 weeks gestationor more. This study aims to describe the characteristics of pregnant women with PEB in theRose Room RSUD dr. M. Yunus Bengkulu 2013. This study used a descriptive researchmethod. The population in this study, all pregnant women with PEB, amounting to 238 peopleand sampling a total sampling. Secondary data were analyzed using univariate. The results ofthis study showed that almost half of pregnant women who experience PEB aged <20 yearsamounted to 109 persons (45.8%), almost half of pregnant women are primigravidanumbering 111 people (46.6%), 238 pregnant mothers throughout the PEB experience withgestational age> 28 weeks, and almost half of pregnant women who experience PEB primaryeducation amounted to 118 people (49.6%).